Discovery and empire the French in the South Seas - West-Sooby, John (The University of Adelaide Press, 2013)
It was not until the eighteenth century that France began sending mariners to the southern oceans on a regular basis, and by that time a new maritime power had begun to emerge: Great Britain. Together, these two nations would play a decisive role in determining the configuration of these little known parts of the globe, and particularly of the Pacific, which had for so long been the almost exclusive preserve of Spain
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte; Kolonie; Frankreich; France / Colonies / Oceania / History; Oceania / Discovery and exploration / French; France / Territories and possessions / History; France / Relations / Oceania; Oceania / Relations / France; Oceania / Colonization / History